Lipid and Volatile Profiles of Various Goat Primal Cuts: Aspects of Nutritional Value and Flavor/Taste Attributes - Nachomkamon Saengsuk; Papungkorn Sangsawad; Pramote Paengkoum; Jaksuma Pongsetkul (My University, 2024)
The lipid and volatile profiles of goat primal cuts (shoulder, rib, loin, breast, and leg), as well as their potential impact on nutritional and flavor/taste attributes, were investigated. The breast cuts had the lowest protein but the highest fat content. Triacylglycerol was the predominant lipid in all cuts (82.22-88.01%), while the breast cuts had the lowest triacylglycerol and the highest diacylglycerol and free fatty acids. Also, the highest unsaturated fatty acid (UFA), both monounsaturated fatty acid (MUFA) and polyunsaturated fatty acid (PUFA), was obtained in the breast cuts. These findings correlated well with the highest peroxide value (PV) and thiobarbituric acid reactive substances (TBARS) value. The volatile profiles of the various grilled cuts indicated that the breast and leg cuts had similar volatiles, with higher amounts of alcohol, aldehyde, ketone, and ester than others, which could explain the flavor oxidation by lipid and off-flavors in spoiled meat. While the shoulder, rib, and loin cuts had higher amounts of nitrogen-containing compounds. The highest sulfur-containing and hydrocarbon compounds were also observed in the shoulder cuts, which are mainly formed during the Maillard reaction and responsible for the cooked meat flavor. This investigation revealed that each cut of goat meat has a varied composition, especially in lipids and volatile compounds. Thus, meat quality differs in terms of nutritional aspects and flavor/taste characteristics, enabling consumers to select nutritious or proper cuts for their cooking to achieve the most satisfaction from goat meat consumption.
Keywords: Lipid Oxidation; Loin; TBARS; Peroxide value; Thiobarbituric acid; Meat and Animal Product Quality